Estudo de técnicas híbridas de desidratação de resíduos de acerola - Nogueira, Geraldo Daniel Ribeiro (2016)
Fruit growing is a solid commercial activity in Brazil. Over 41 million tons of fruits are produced per year, placing it behind only China and India. Fruits can be sold fresh or processed, as pulps, juices and jams. During the processing, agro-industrial residues are generated. It is estimated that more than 40% in volume of the fruits sent to be processed will become agro-industrial residues. These residues are constituted by a heterogeneous mix of seeds, peels and residual pulp. Which are rich in ascorbic acid, tocopherols, carotenoids and phenolic compounds. Industries and producers face the problem of its disposal. Although it is a biodegradable material, the residues require some time to decompose. Within this context, hybrid drying techniques rise as an alternative to reuse these residues turning it into flour aiming food products. Therefore, in this study acerola residue was characterized by its physical-chemical properties, maximum moisture content for safe storage and and the use of hybrid dehydration techniques for its possible reuse. It was found that acerola residue is a rich source of nutrients and bioactive compounds and when it has moisture content below 26% does not present favorable conditions for microbiological growth. Then, drying experiments were performed in two different hybrid dryers: vacuum microwave and fixed-bed convective dryer aided by infrared radiation. Preliminary tests showed that the use of microwave was viable as a dehydration method, which caused an increase in some compounds, such as total flavonoids content. It was noticed that ascorbic acid degradation due to oxidation was reduced when vacuum was added to the process. Several pre-treatments were tested in order to enhance vacuum microwave drying. Among which, the pre-treatment where the residue was immersed in ethanol got the most prominent results including average reduction of 54% of the process and ascorbic acid content increases. The Overhults model fitted better the experimental drying kinetic data for acerola residue dehydration in both the microwave and in vacuum microwave (with and without pretreatment). It was also found that the use of infrared radiation had a positive effect in order to minimize heterogeneity characteristic of dehydration in a fixed bed.